Public Relations Strategy of SMKN 1 Bengkulu City in Developing the School's Image - Septa, Anggela Dwi; Octaviani, Vethy; Yanto, Yanto (Journal of Multidisciplinary Research, 2025)
This study aims to determine how public relations strategies develop the image of SMKN 1 Kota Bengkulu. The method used in this study is descriptive qualitative. There are four (4) informants in this study, consisting of one (1) key informant and three (3) main informants. Data collection methods include observation, interviews, and documentation. Based on the research results and discussion using the Cutlip-Center-Broom theory of professional public relations practitioners (Morissan, 2008): (1) Defining the problems, (2) Planning and programming, (3) Taking action and communicating. (5) Evaluating the program.